Multiple Organ Lesions in a Case of Contamination With Multiple Radionuclides After 38 Years - Huahui Bian; Youyou Wang; Weibo Chen; Yusong Zhang; Zhixiang Zhuang; Rui Xia; Hong Dai; Junchao Feng; Wangyang Pu; Lei Chen; Wu Cai; Wentao Hu; et al. (SAGE Publishing, 2018)
The patient was contaminated with multiple radionuclides 38 years ago due to an accident. To investigate the effects of radionuclide contamination on humans, he has been followed up by examinations for many years. Long-term effects gradually emerge in these years. Lung cancer was diagnosed by medical examinations. Besides, chronic gastritis with intestinal metaplasia was indicated by gastroscopic biopsies, while colorectal polyps found by colonoscopy. All 13 colorectal polyps were removed, and radical surgery for lung cancer was performed. Fortunately, pathological examinations indicated that it was early lung cancer. The ground glass nodule (GGN) in left lung identified during the follow-up will be resected when needed. It is speculated that multiple manifestations of the patient may be related to radiation, and different lesions in the organs may be related to systemic adaptive response. However, longer follow-up is needed due to a lack of effective and direct evidence. This work is expected to provide experiences for similar patients' treatment and follow-up.